Diagnosis of Mondor's Disease in the Emergency Department with Bedside Ultrasound. (18th January 2015) - O'Neal, J. Michael; Castleberg, Erik; Dinh, Vi Am
Abstract : Mondor's disease is a rare condition characterized by a superficial thrombophlebitis that can occur in the thoracoabdominal and genital areas. Findings with ultrasound in penile Mondor's disease are readily measurable: a noncompressible penile vein without flow and absence of tears of the corpus cavernosum or tunica albuginea, hematoma, or evidence of fracture of the penis. We present a case of Mondor's disease, diagnosed with bedside ultrasound, in the emergency department. Ultrasonography is readily available within the emergency department, and we suggest its use in aiding diagnosis of genitourinary disorders such as Mondor's disease.